1978
DOI: 10.4141/cjas78-046
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Hormone Levels in Beef Cows During Pregnancy Terminating in Normal Calving or Abortion and With Single or Multiple Ovulation

Abstract: AorrexouN, V., MATroN, P. eNo Dupoun, J. J. 1978. Steroid

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

1979
1979
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 1 publication
2
5
0
Order By: Relevance
“…In addition, the result that there was no significant difference between the profiles of untreated singleton and twin-bearing cows is in agreement with some earlier reports [11,15] but contradictory to others [9,14]. Reduced gestational length in twin-bearing cows and also the significantly elevated progesterone concentration found throughout the gestation period in treated cows are comparable with earlier investigations [9,14].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In addition, the result that there was no significant difference between the profiles of untreated singleton and twin-bearing cows is in agreement with some earlier reports [11,15] but contradictory to others [9,14]. Reduced gestational length in twin-bearing cows and also the significantly elevated progesterone concentration found throughout the gestation period in treated cows are comparable with earlier investigations [9,14].…”
Section: Discussionsupporting
confidence: 90%
“…In general the plasma progesterone secretory profile of untreated singleton cows reported here is consistent with that of several other authors [9][10][11]15] but different from that reported elsewhere [13,14]. In addition, the result that there was no significant difference between the profiles of untreated singleton and twin-bearing cows is in agreement with some earlier reports [11,15] but contradictory to others [9,14].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Although the progesterone concentration is identified commercially as an aid to the diagnosis of pregnancy in the cow, it is not pregnancy-specific and its accuracy is variable (20). In addition, reports on the effect of the number of fetuses being carried on progesterone concentration are conflicting (11,(21)(22)(23), suggesting that bPAG, in common with PSPB (8,12,13) and PSP-60 (7), offers a better serological test for the diagnosis of pregnancy and for distinguishing the number of fetuses being carried. The large individual variation in bPAG concentrations at all stages of gestation in the present study could be attributable to the limited number of animals used.…”
Section: Discussionmentioning
confidence: 99%